Permalink Submitted by Anonymous on April 24, 2015

I saw a demonstration of this sum recently. It went like this:
S=1-1+1-1+...
=1-(1-1+1-...)
the periods indicating a continuation to infinity, it is assumed that:
S=1-S
2S=1
S=1/2

Then again, the alternating harmonic series converges to ln2 but by rearranging the terms in the equation, it also converges to (ln2)/2 and (ln2)/4 and so forth. The problem in your reasoning is that you take a partial sum as reference. I know that it's counter-intuitive just like 0.00000...1= 0 but the reason it gives that result is only because the sum is infinite. The moment it becomes finite, these results all go wrong.

## I saw a demonstration of this

I saw a demonstration of this sum recently. It went like this:

S=1-1+1-1+...

=1-(1-1+1-...)

the periods indicating a continuation to infinity, it is assumed that:

S=1-S

2S=1

S=1/2

Then again, the alternating harmonic series converges to ln2 but by rearranging the terms in the equation, it also converges to (ln2)/2 and (ln2)/4 and so forth. The problem in your reasoning is that you take a partial sum as reference. I know that it's counter-intuitive just like 0.00000...1= 0 but the reason it gives that result is only because the sum is infinite. The moment it becomes finite, these results all go wrong.